Development of a Novel Bioelectrochemical Filter for Particulate-rich Wastewater Treatment - Mohammadi Khalfbadam, Hassan (Curtin University, 2016)
This thesis explored the use of bioelectrochemical systems (BES) technology for particulate-rich wastewater treatment such as those emanating from waste stabilisation ponds (WSPs). The development of a novel “filter-type” BES configuration enables the wastewater industry to effectively manage unwanted discharge of particulate solids, particularly for the management of algae discharge in WSPs. The process developed may become a platform technology for BES to be embraced by other industries for treatment of waste organic solids.